Mitigation of condensed tannins found in sericea lespedeza (Lespedza cuneata) - Eckerle, Gregory J. (Kansas State University, 2011)
Sericea lespedeza (SL; Lespedeza cuneata) is classified as an invasive plant throughout the Great Plains. It infests over 600,000 acres in Kansas. Increasing grazing pressure on SL may reduce seed production and slow the spread of the plant; however, intake of SL by grazing beef cattle is poor, due to the presence of tannins in the plant. Condensed tannins reduce protein digestion by ruminants and may also decrease plant palatability. Detailed study of the appetite-suppressing effects of SL under controlled conditions is essential in order to develop appropriate strategies to increase grazing pressure on this plant. Such information could lead to a degree of biological control of this noxious weed using domestic herbivores. We compared intakes of tallgrass prairie hay by beef cows when hay was either uncontaminated or heavily contaminated by SL. Beef cows fed contaminated hay exhibited a profound aversion to compared to similar uncontaminated hay. Furthermore, differences in voluntary DMI between contaminated and uncontaminated hays of similar chemical composition were manifested rapidly after introduction of contaminated hay into beef cow diets. Supplementation with corn steep liquor (CSL) increased tolerance of beef cows for SL. It ameliorated the negative consequences of tannin consumption in a dose-dependent manner when fed to beef cows in confinement. The beef cows in our study had only limited opportunity to selectively avoid SL because it was offered in chopped form and in a mixture with other forage species. It was unknown if beef cattle supplemented with CSL would readily consume forage contaminated by SL when uncontaminated forage was available simultaneously. Therefore, we examined the effects of CSL fed to beef cows on voluntary selection of tallgrass prairie hay contaminated by SL when uncontaminated tallgrass prairie hay was also available. Supplemental CSL (0.6 kg DM/d) increased both acceptance of and tolerance for SL by beef cows. It ameliorated some of the negative consequences of tannin consumption on digestible DM intake. In addition, voluntary consumption of SL-contaminated forage increased by 25% in supplemented vs. unsupplemented beef cows. It is unknown if supplemental CSL can promote voluntary selection of actively-growing SL by beef cattle grazing native rangeland in the Kansas Flint Hills.
Keywords: Cattle; Sericea; Tannins; Forage; Animal Sciences (0475)